Consequences of Mrp2 deficiency for diclofenac toxicity in the rat intestine ex vivo. Issue 1 (February 2015) - Niu, Xiaoyu; de Graaf, Inge A.M.; van de Vegte, Dennis; Langelaar-Makkinje, Miriam; Sekine, Shuichi; Groothuis, Geny M.M.
Highlights Mrp2 deficient rat intestine ex vivo is intrinsically less sensitive to diclofenac toxicity. Lower uptake of diclofenac contributes to the lower diclofenac toxicity in Mrp2− rat intestine. Adaptive changes in metabolism and transport in Mrp2− rats are different between liver and intestine. Precision cut intestinal slices allow studying drug-induced toxicity in the gut without interference of liver.